Kalimat Imperatif dalam Cerpen Hanya Rindu Karya Faisal Oddang dan Sahabat Inna (Kajian Pragmatik) - Irwan Siagian; Ayu Herfina; Azharia Putriningtyas (Journal on Education, 2023)
Short stories as a form of prose literary work are expected to generate positive values for their readers, so that they can be sensitive to problems related to social life and encourage good behavior. Short stories usually tell about pictures of the reality of human life and the environment around it. This research is focused on the form and meaning of imperative sentences in a collection of short stories by Faisal Oddang and Inna's friend. The aim of this research is to find out the form and meaning of imperative sentences in a collection of short stories by Faisal Oddang and Inna's best friend. This research uses qualitative descriptive data analysis techniques. . Data collection was carried out using the method of observing through note-taking techniques. From the results of the research, it shows that there is a conclusion in a collection of short stories by Faisal Oddang and Inna's friend, which shows that imperative sentences are used in the short stories. The form of imperative sentences consists of subtle imperative sentences, imperative sentences of requests or requests, imperative sentences of solicitation or hope, imperative sentences of prohibition, and imperative sentences of omission.